Telltale signs of hansen\'s disease: discolored, hypoesthetic patch and deformities of the hand - Uneza Husain; Imtiaaz Beg (Journal of Research in Applied and Basic Medical Sciences, 2024)
Leprosy (Hansen's Disease) is a crippling, devastating disease affecting skin, eyes, and nerves; the etiological agent being Mycobacterium leprae. India, Brazil, and Indonesia account for the majority of cases globally. Early diagnosis and prompt treatment by multidrug regimen are the mainstays of management of this chronic infectious disease which is transmitted by respiratory route and skin to skin contact from cases of leprosy. We report a case of leprosy in a 14-year-old boy in Uttar Pradesh, manifesting as hypopigmented hypoesthetic patch with thickened ulnar nerve, emphasizing the fact that the disease is still endemic in states like Uttar Pradesh; hence it is important to do the hawk-eyed examination to avoid missing any hidden case.